A lightweight micro-nano porous three-dimensional high-heat protection material and its preparation method
By using the blended yarn and fabric structure design of flame-retardant prefabricated fibers and high-performance fibers in high-thermal protection materials, and combining high-temperature treatment to form a multi-dimensional three-dimensional micro-nano porous structure, the problems of difficulty in the processing process and degradation of thermal protection performance in existing materials are solved, and the lightweight, high-thermal protection and smoke suppression performance are improved.
Patent Information
- Application Number
- CN202411887715.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-04
AI Technical Summary
The existing high-thermal protection materials are difficult to process, have low production efficiency, and have problems such as degraded thermal protection performance and insufficient smoke suppression performance.
The blended yarn of flame-retardant prefabricated fibers with high-performance flame-retardant fibers, flame-retardant superwater-absorbent fibers and flame-retardant ultrafine hydrophobic fibers is used to spin. A multi-dimensional and three-dimensional micro-nano porous structure is formed through fabric structure design and high-temperature treatment.
It has achieved the improvement of lightweight and high-thermal protection performance, reduced processing difficulty and production costs, and enhanced smoke suppression performance and comfort.
Smart Images

Figure CN119753926A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation of high-heat protection multifunctional textile materials, and in particular to a lightweight micro-nano porous three-dimensional high-heat protection material and a preparation method thereof. Background Art
[0002] High-heat protective clothing is one of the most widely used types of protective clothing. High-heat protective clothing refers to protective equipment that can prevent the clothing itself from being ignited or slow down and stop burning in extreme thermal environments. Extreme thermal environments mainly include strong flame convection and radiation heat, high-temperature combustion or object contact heat, molten metal splashes, steam jets, high-temperature gas convection heat, and high-temperature liquid splashes. The thermal insulation principle of high-heat protective clothing is mainly to reduce the speed of heat transfer to human skin, thereby delaying the time it takes for the skin to burn. It can isolate heat sources and open flames from the human body, thereby preventing overheating injuries, heat stroke or burns, etc., avoiding high temperature or ultra-high temperature heat sources from causing harm to the human body, and maintaining the personal safety of the wearer. It is widely used in work clothes in firefighting, military, emergency rescue, petrochemical, natural gas, food processing and other industries.
[0003] At present, high-heat protection materials are mainly realized through three technical measures: fiber microstructure construction, multi-layer fabric composite design, and coating and impregnation.
[0004] In terms of fiber microstructure construction, the most typical technical means is to prepare various microstructure or aerogel fibers. For example, patent CN114481357A discloses a microstructure fiber, which consists of a cladding layer and a core layer. After the fiber is formed, it is heated to give the fiber a microstructure. Supercritical or freeze-drying technology can also be used to obtain aerogel fibers with a porous network structure. Finally, the prepared microstructure or aerogel fiber is processed into various fabrics using woven, non-woven or knitted technology.
[0005] In terms of multi-layer fabric composite design, it is mainly achieved with the help of adhesives or fabric structure design. For example, CN112221027B discloses a flame-retardant and heat-insulating fabric for fire escape emergency, which is composed of three single-layer fabrics, namely a hydrogel dressing layer, a heat-insulating non-woven fabric layer and a flame-retardant non-woven fabric layer, connected by adhesive bonding or hot-melt reinforcement. For example, CN116423938A discloses a thermal protection fabric with a multi-dimensional composite structure. The fabric has three layers, from the outside to the inside, respectively, an inorganic fiber primary protection layer, a thermal and moisture comfort regulating layer, and an aerogel thermal secondary protection layer, and the thermal and moisture comfort regulating layer is connected and interlaced with the other two layers to form a whole.
[0006] In terms of the coating and impregnation technology, CN108221397B provides a method for preparing a fire-fighting heat-insulating metallized coating fabric, in which a flame-retardant base fabric is calendered and humidified, coated with a flame-retardant polyurethane silver paste solution, and then dried to obtain a fire-fighting heat-insulating metallized coating fabric.
[0007] The existing technology improves the thermal protection performance of fabrics by constructing fiber microstructures, designing multi-layer fabric composites, and using coating and impregnation technology, but there are mainly the following technical deficiencies.
[0008] First, after preparing the raw materials of microstructure or aerogel fibers, when processing the fabric, the tensile, elastic, friction and other properties of the fibers are reduced due to the large number of micropores in the fiber structure, making it difficult to spin and weave the microstructure or aerogel fibers, and difficult to industrialize and mass-produce. At the same time, during the long textile process, the mechanical friction and extrusion of such fibers will cause damage to the fiber microstructure, resulting in a sharp decline in the thermal protection performance of the final fabric.
[0009] Second, when preparing micro-nano structures or aerogel fibers, the existing technology has a long process flow. Especially when preparing aerogel fibers, the more mature ones currently use supercritical or freeze-drying technology. The reaction conditions are harsh, and it is difficult to achieve continuity in the process of solvent replacement and drying, resulting in low production efficiency and affecting large-scale industrial applications. In addition, the mechanical fragility and structural instability of traditional aerogel fibers limit their widespread use in practical applications. In addition, when multi-layer fabrics are composited, most of them are simply physically stacked. While increasing the total mass of the fabric, the thermal protection effect of the fabric is limited, making it difficult to achieve lightweight and high-heat protection.
[0010] Third, the thermal protection fabric obtained by coating and impregnation technology has poor air permeability. The fabric is easily damaged during processing and wearing, and is not resistant to washing, resulting in a decrease in its thermal protection performance. In addition, existing high-temperature flame-retardant protective materials, such as CN109208154A, are made by blending 30% to 65% of nitrile chlorofiber fibers, 30% to 65% of flame-retardant regenerated cellulose fibers, and 5% to 25% of para-aramid fibers to form nitrile chlorofiber blended flame-retardant, high-temperature antistatic fabrics. Since the fabric contains nitrile chlorofiber, a large amount of smoke containing toxic and corrosive chemicals will be produced when it burns, and inhalation of toxic gases leading to coma and suffocation is also the main cause of casualties in fires. Therefore, the smoke suppression performance of flame-retardant and high-temperature protective materials needs to be improved urgently.
[0011] It can be seen that the thermal protection fabrics developed by existing technologies, which are developed by using microstructured or aerogel fibers, are difficult to process, have low production efficiency, and suffer from performance degradation; the thermal protection improvement of multi-layer superimposed fabrics is limited, and it is difficult to achieve both light weight and high heat protection. Toxic smoke will be generated during combustion, and smoke suppression and comfort need to be further improved. Summary of the invention
[0012] In view of the above-mentioned deficiencies in the prior art, an object of the present invention is to provide a method for preparing a lightweight micro-nano porous three-dimensional high-heat protective material.
[0013] The present invention provides a method for preparing a lightweight micro-nano porous three-dimensional high-heat protection material, the steps comprising:
[0014] Step 1, preparation of flame-retardant prefabricated fibers: first, nano-sol composite smoke suppression flame retardant and cross-linking agent are sequentially added to cellulose ionic liquid solution and stirred to obtain cross-linked flame-retardant cellulose ionic liquid solution; then, a certain proportion of heat-expandable microsphere foaming agent is added to the cross-linked flame-retardant cellulose ionic liquid solution and stirred to obtain spinning solution, then the spinning solution is filtered and degassed in sequence and placed in a wet spinning device, and the spinning solution is extruded from the spinneret under a nitrogen pressure of 0.5 MPa, and flame-retardant prefabricated fibers are obtained through coagulation, hot stretching, cutting, oiling, packaging and other processes;
[0015] The average particle size of the nano-sol composite flame retardant is 200nm-300nm; the nano-sol composite smoke suppression flame retardant comprises a mixture of bisphenol modified phosphate ester oligomer, hydroxymethyl phosphonic acid guanidine urea, phosphorus heterocyclic methoxy, ferrous oxalate, calcium phosphomolybdate and dihydroxy metal composite oxide-magnesium aluminum hydroxide;
[0016] Step 2, spinning of blended yarn: the flame retardant prefabricated fiber is mixed with the high-performance flame retardant fiber, the flame retardant super absorbent fiber, and the flame retardant superfine hydrophobic fiber respectively, and the three mixtures are respectively subjected to the processes of oiling and moistening, premixing, carding and combing, drawing, roving, spun yarn, winding, doubling, twisting, and steaming yarn to spin yarn I, yarn II, and yarn III respectively;
[0017] Step 3, preparation of base fabric: through fabric structure design, yarn I, yarn II and yarn III are warped, sizing, reeded, weaved and repaired in sequence to obtain a multi-layer base fabric, wherein the outermost layer of the multi-layer base fabric is a flame retardant layer composed of yarn I, the middle layer is a super absorbent layer composed of yarn II, and the innermost layer is a hydrophobic comfort layer composed of yarn III;
[0018] Step 4, preparation of lightweight high-heat protective material: After the base fabric prepared in step 3 is desized, dyed, and stretched and shaped, the inner surface of the fabric is then subjected to a sanding process, and then subjected to a high-temperature treatment, so that the heat-expandable microsphere foaming agent evenly distributed in the flame-retardant prefabricated fiber matrix expands when heated to form a multi-dimensional lightweight high-heat protective material.
[0019] Furthermore, in the cross-linked flame-retardant cellulose ionic liquid solution in step 1, the nano-sol composite smoke suppression flame retardant comprises 15 to 25 parts, the cross-linking agent comprises 3 to 5 parts, and the rest is cellulose ionic liquid solution.
[0020] Furthermore, in the spinning solution in step 1, the thermal expansion microsphere foaming agent accounts for 10 to 25 parts, and the average particle size of the thermal expansion microsphere foaming agent is 300 nm to 400 nm; the rest is a cross-linked flame-retardant cellulose ionic liquid solution.
[0021] Furthermore, the nano-sol composite smoke suppression flame retardant in step 1 includes a mixture of bisphenol modified phosphate ester polymer, hydroxymethyl phosphonic acid guanidine urea, phosphorus heterocyclic methoxy, ferrous oxalate, calcium phosphomolybdate and dihydroxy metal composite oxide-magnesium aluminum hydroxide.
[0022] Furthermore, the nanosol composite smoke suppressant and flame retardant in step 1 comprises 10 to 20 parts of bisphenol-modified phosphate ester polymer, 10 to 20 parts of hydroxymethylphosphonic acid guanidine urea, 20 to 35 parts of phosphorus heterocyclic methoxy, 8 to 15 parts of ferrous oxalate, 15 to 25 parts of calcium phosphomolybdate and 8 to 15 parts of dihydroxy metal composite oxide-magnesium aluminum hydroxide; the average particle size of the nanosol composite smoke suppressant and flame retardant is 200 nm to 300 nm.
[0023] Furthermore, the cross-linking agent in step 1 comprises 45 to 65 parts of ammonium bicarbonate and 35 to 55 parts of ammonium acetate.
[0024] Furthermore, in the hot stretching process in step 1, the hot stretching temperature is 110° C. to 120° C., and the stretching ratio is 1.5 to 3.0 times.
[0025] Furthermore, the high-performance flame-retardant fiber in step 2 includes a mixture of various fibers including aromatic sulfone fiber, polyphenylene sulfide fiber, polyimide fiber, meta-aramid fiber and para-aramid fiber.
[0026] Furthermore, the yarn I in step 2 contains 30 to 50 parts of flame-retardant prefabricated fibers, 20 to 40 parts of aromatic sulfone fibers, 25 to 45 parts of polyphenylene sulfide fibers, and 25 to 40 parts of polyimide fibers.
[0027] Furthermore, the yarn II described in step 2 contains 25 to 45 parts of flame-retardant super absorbent fibers, 30 to 50 parts of flame-retardant prefabricated fibers, 20 to 50 parts of meta-aramid fibers, and 5 to 15 parts of para-aramid fibers.
[0028] Furthermore, the yarn III described in step 2 comprises 25 to 45 parts of flame-retardant ultrafine hydrophobic fibers, 30 to 50 parts of flame-retardant prefabricated fibers, 20 to 50 parts of meta-aramid fibers, and 5 to 15 parts of para-aramid fibers;
[0029] Furthermore, the linear density of yarn I described in step 2 is 11.81tex×2~15.54tex×2, the linear density of yarn II is 9.84tex×2~11.81tex×2, and the linear density of yarn III is 11.81tex×2~13.12tex×2.
[0030] Furthermore, the yarn steaming process temperature in step 2 is 80°C to 100°C.
[0031] Furthermore, the fabric structure in step 3 is formed by the middle layer being interwoven with the outer layer and the inner layer by means of inner warp knotting outer weft and outer warp knotting inner weft respectively; wherein the fabric structure of the outer layer, middle layer and inner layer is plain weave or twill weave.
[0032] Furthermore, in step 3, the warp density of the fabric is 660 to 710 strands / 10 cm, and the weft density is 575 to 625 strands / 10 cm.
[0033] Furthermore, in step 3, the arrangement ratio of the outer layer, middle layer and inner layer fabric yarns is 1:1:1 to 4:2:3.
[0034] Furthermore, the drying temperature of the sizing process described in step 3 is 100°C to 120°C.
[0035] Furthermore, the mass per unit area of the base fabric in step 3 is 300 g / m 2 ~360g / m 2 .
[0036] Furthermore, the mesh number of the sandpaper in step 4 is 400-500 mesh, the vehicle speed is 12 m / min-18 m / min, the grinding roller speed is 850-950 rpm, and the pressure is 0.2 MPa-0.4 MPa.
[0037] Furthermore, the high temperature treatment in step 4 is performed at a temperature of 140°C to 160°C.
[0038] On the other hand, the present invention also provides a lightweight micro-nano porous three-dimensional high-heat protection material prepared using the aforementioned preparation method.
[0039] The beneficial effects of the present invention are:
[0040] The lightweight micro-nano porous three-dimensional high-heat protection material described in the present invention, in the process of preparing and processing flame-retardant prefabricated fibers, the heat drawing temperature (110°C-120°C), the sizing drying temperature (100°C-120°C), and the steaming temperature (80°C-100°C) are all lower than the thermal expansion temperature (130°C-150°C) of the thermal expansion microsphere foaming agent. In the process of spinning and weaving the flame-retardant prefabricated fibers to form a base fabric, it does not expand, reducing the processing difficulty caused by the poor physical and mechanical properties of the microstructure or aerogel fibers. At the same time, it also avoids the direct use of microstructure or aerogel fibers, and the long process from spinning to weaving. The fiber is damaged by the micro-nano structure during the combing, drawing, and twisting process, ensuring the thermal protection performance. It solves the technical problem that traditional materials with micro-nano structures such as aerogel fibers are difficult to industrialize on a large scale due to mechanical fragility and structural instability.
[0041] The lightweight micro-nano porous three-dimensional high-heat protective material described in the present invention creatively performs high-temperature heating treatment on the final heat protective material, so that the flame-retardant prefabricated fibers in the formed material expand. At the same time, the high-temperature treatment temperature is 140°C to 160°C, which is much lower than the lowest heat resistance temperature of the prefabricated flame-retardant fiber matrix and other fibers. It does not cause irreversible damage to the protective material, but only thermally expands the flame-retardant prefabricated fibers to form a lightweight micro-nano porous three-dimensional high-heat protective material.
[0042] The high-heat protection material developed by the present invention is a fully mixed fiber from each spinning process, and the flame-retardant prefabricated fibers are evenly distributed. In terms of microscopic morphology, the high-heat protection material is uniformly distributed with various micro-nano-sized closed independent (closed-cell) and mutually interpenetrating (open-cell) mixed pore structures. The air in the mixed pore structure forms a unique gas chamber with the bubble wall. The unique properties of the air give the material low density and low thermal conductivity to improve the thermal insulation performance of the protection material. In terms of macroscopic morphology, when the special multi-layer composite structure fabric of the present invention encounters a heat source, the heat is reflected multiple times in the multi-layer structure of the protection material to form heat dissipation, which can further improve the thermal insulation performance of the protection material. At the same time, the constructed micro-nano porous structure is creatively and effectively combined with the multi-structure of the macroscopic protection material. Through the "micro-meso-macro" cross-scale synergistic effect, the thermal insulation performance of the protection material is significantly improved, which solves the defect that the thermal protection performance of the laminated composite fabric developed by simply increasing the number of material layers is not significantly improved.
[0043] The self-made flame-retardant prefabricated fiber of the present invention directly undergoes chemical cross-linking reaction with the fiber matrix through heat expansion microsphere foaming agent, nano sol flame retardant and fiber matrix. The self-made flame-retardant prefabricated fiber is almost the same as the commonly used textile fiber in performance when not subjected to heat expansion treatment. When the flame-retardant prefabricated fiber is blended with other fibers, it is mixed through multiple processes, and the flame-retardant prefabricated fiber is evenly distributed. Theoretically, there is no upper limit to the addition amount, and an addition amount of 100% can be achieved. After high-temperature treatment, the material can be distributed with more micro-nano porous structures, so that the protective material is lightweight and high heat protection is achieved.
[0044] When preparing flame-retardant prefabricated fibers, the present invention adds ferrous oxalate, calcium phosphomolybdate and dihydroxy metal composite oxide-magnesium aluminum hydroxide smoke suppressant flame retardant to the nanosol composite smoke suppressant halogen-free flame retardant. The smoke suppressant flame retardant promotes carbonization by cross-linking in the condensed phase, converts carbon in the polymer into carbon monoxide and carbon dioxide, and can dilute combustible gases and smoke, thereby reducing the amount of carbon black formed and playing a smoke suppressant role, or the aluminum oxide and magnesium oxide formed during the heating process have a large surface area and can adsorb smoke. It can be seen that the present invention creatively changes its combustion mode through the flame retardant-smoke suppression synergistic effect, and relies on smoke suppression and flame retardant principles such as covering effect, transfer effect, inhibition of free radicals, and accelerated carbonization, reduces the amount of smoke by reducing the content of combustibles, and utilizes synergistic effects to achieve a composite smoke suppression and flame retardant effect.
[0045] When designing the three-dimensional high-heat protective material structure, the present invention arranges a flame retardant layer, a moisture absorption layer and a comfort layer from the outside to the inside. The outermost flame retardant layer prevents the burning and spreading of flames and prevents molten dripping, thereby achieving the structural integrity and functional maintenance of the protective clothing when working in a hot environment. The super absorbent fiber in the middle moisture absorption layer can absorb and store the sweat produced by the human body. The innermost comfort layer is composed of ultrafine fibers. After being sanded, a plush texture is formed on the surface of the material, making it soft, comfortable and skin-friendly to the touch, thereby improving the comfort of the protective material.
[0046] It can be seen that the preparation process of the present invention is short, green and environmentally friendly, and easy to industrialize. The prepared protective material is lightweight, has excellent smoke suppression and flame retardancy, and has excellent heat insulation and moisture absorption properties and is comfortable to wear. It can be widely used in the development of lightweight and high-heat protective clothing in high-temperature industries such as firefighting and petrochemicals. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0048] Figure 1This is the SEM image of the flame retardant prefabricated fiber in Example 1.
[0049] Figure 2 This is a SEM image of the micro-nano flame-retardant fiber formed by high-temperature expansion in Example 1. DETAILED DESCRIPTION
[0050] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0051] The flame retardant super absorbent fiber in the present invention was purchased from British Technical Absorbent Products Co., Ltd., and the flame retardant superfine hydrophobic fiber was purchased from Qingdao Xinwei Textile Development Co., Ltd.; the heat-expandable microsphere foaming agent was purchased from Polychem of the United States, model 186DU20; bisphenol modified phosphate polymer (BDP) was purchased from Hai'an Petrochemical Plant in Jiangsu Province; hydroxymethyl phosphonic acid guanidine urea was purchased from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd.; zinc stannate was purchased from Hubei Xingyan New Materials Technology Co., Ltd.; phosphorus heterocyclic methoxy was purchased from Shandong New Kinetic Energy Chemical Co., Ltd.; ferrous oxalate was purchased from Jinan Kaichuang Chemical Co., Ltd.; calcium phosphomolybdate was purchased from Shanghai Youpeng Chemical Co., Ltd.; dihydroxy metal composite oxide-magnesium aluminum hydroxide was purchased from Hebei Yuechao Wear-resistant Materials Co., Ltd.; ammonium bicarbonate was purchased from Shandong Xinyi Biotechnology Co., Ltd.; and ammonium acetate was purchased from Weifang Youlan Chemical Co., Ltd.
[0052] Example 1
[0053] This embodiment provides a method for preparing a lightweight micro-nano porous three-dimensional high-heat protection material, the steps comprising:
[0054] Step 1, preparation of flame-retardant prefabricated fibers: first, nano-sol composite smoke suppression flame retardant and cross-linking agent are sequentially added to cellulose ionic liquid solution and stirred to obtain cross-linked flame-retardant cellulose ionic liquid solution; then, a certain proportion of heat-expandable microsphere foaming agent is added to the cross-linked flame-retardant cellulose ionic liquid solution and stirred to obtain spinning solution, then the spinning solution is filtered and degassed in sequence and placed in a wet spinning device, and the spinning solution is extruded from the spinneret under a nitrogen pressure of 0.5 MPa, and flame-retardant prefabricated fibers are obtained through coagulation, hot stretching, cutting, oiling, packaging and other processes;
[0055] Step 2, spinning of blended yarn: the flame retardant prefabricated fiber is mixed with the high-performance flame retardant fiber, the flame retardant super absorbent fiber, and the flame retardant superfine hydrophobic fiber respectively, and the three mixtures are respectively subjected to the processes of oiling and moistening, premixing, carding and combing, drawing, roving, spun yarn, winding, doubling, twisting, and steaming yarn to spin yarn I, yarn II, and yarn III respectively;
[0056] Step 3, preparation of base fabric: through fabric structure design, yarn I, yarn II and yarn III are warped, sizing, reeded, weaved and repaired in sequence to obtain a multi-layer base fabric, wherein the outermost layer of the multi-layer base fabric is a flame retardant layer composed of yarn I, the middle layer is a super absorbent layer composed of yarn II, and the innermost layer is a hydrophobic comfort layer composed of yarn III;
[0057] Step 4, preparation of lightweight high-heat protective material: After the base fabric prepared in step 3 is desized, dyed, and stretched and shaped, the inner surface of the fabric is then subjected to a sanding process, and then subjected to a high-temperature treatment, so that the heat-expandable microsphere foaming agent evenly distributed in the flame-retardant prefabricated fiber matrix expands when heated to form a multi-dimensional lightweight high-heat protective material.
[0058] The cross-linked flame-retardant cellulose ionic liquid solution in step 1 contains 20 parts of nanosol composite smoke suppression flame retardant, 5 parts of cross-linking agent, and the rest is cellulose ionic liquid solution.
[0059] The spinning stock solution in step 1 contains 25 parts of heat-expandable microsphere foaming agent, the average particle size of the heat-expandable microsphere foaming agent is 300 nm; the rest is cross-linked flame-retardant cellulose ionic liquid solution.
[0060] The nanosol composite smoke suppressant and flame retardant described in step 1 contains 10 parts of bisphenol-modified phosphate ester polymer, 20 parts of hydroxymethylphosphonic acid guanidine, 30 parts of phosphorus heterocyclic methoxy, 10 parts of ferrous oxalate, 15 parts of calcium phosphomolybdate and 15 parts of dihydroxy metal composite oxide-magnesium aluminum hydroxide. The average particle size of the nanosol composite smoke suppressant and flame retardant is 200nm.
[0061] The cross-linking agent in step 1 comprises 55 parts of ammonium bicarbonate and 45 parts of ammonium acetate.
[0062] In the hot stretching process described in step 1, the hot stretching temperature is 120° C. and the stretching ratio is 2.0 times.
[0063] The yarn I described in step 2 comprises 50 parts of flame-retardant prefabricated fibers, 25 parts of polyphenylene sulfide fibers, and 25 parts of polyimide fibers.
[0064] The yarn II described in step 2 contains 25 parts of flame-retardant super absorbent fibers, 45 parts of flame-retardant prefabricated fibers, 20 parts of meta-aramid fibers, and 10 parts of para-aramid fibers.
[0065] The yarn III described in step 2 contains 25 parts of flame-retardant ultrafine hydrophobic fibers, 45 parts of flame-retardant prefabricated fibers, 20 parts of meta-aramid fibers, and 10 parts of para-aramid fibers.
[0066] The linear density of yarn I described in step 2 is 14.76 tex×2, the linear density of yarn II is 9.84 tex×2, and the linear density of yarn III is 13.12 tex×2.
[0067] The yarn steaming process temperature in step 2 is 100°C.
[0068] The fabric structure described in step 3 is formed by the middle layer being interwoven with the outer layer and the inner layer by means of inner warp knotting outer weft and outer warp knotting inner weft.
[0069] The fabric in step 3 has a warp density of 700 strands / 10 cm and a weft density of 615 strands / 10 cm.
[0070] The arrangement ratio of the outer layer, middle layer and inner layer fabric yarns in step 3 is 4:2:3.
[0071] The drying temperature of the sizing process described in step 3 is 120°C.
[0072] The mass per unit area of the base fabric described in step 3 is 360 g / m 2 The unit area mass ratio of the outer layer, middle layer and inner layer fabrics is 3:2:2.
[0073] The mesh number of the sanded leather described in step 4 is 400 meshes, the vehicle speed is 18 meters per minute, the grinding roller speed is 950 revs per minute, and the pressure is 0.4 MPa.
[0074] The temperature during the high temperature treatment in step 4 is 160°C.
[0075] Figure 1 is a SEM image of the flame retardant prefabricated fiber in Example 1; Figure 2 This is a SEM image of the micro-nano flame-retardant fiber formed by high-temperature expansion in Example 1.
[0076] Depend on Figure 1 It is known that the flame retardant prefabricated fibers before high temperature treatment have uniform texture, high molecular orientation, and excellent mechanical properties, which are not much different from conventional textile fibers;
[0077] Depend on Figure 2 It is known that after high-temperature treatment, the flame-retardant prefabricated fibers will have a micro-nano porous structure in the cross section of the fiber, which is beneficial to the improvement of the thermal protection performance of high-heat protection materials.
[0078] Example 2
[0079] This embodiment provides a method for preparing a lightweight micro-nano porous three-dimensional high-heat protection material, the steps comprising:
[0080] Step 1, preparation of flame-retardant prefabricated fibers: first, nano-sol composite smoke suppression flame retardant and cross-linking agent are sequentially added to cellulose ionic liquid solution and stirred to obtain cross-linked flame-retardant cellulose ionic liquid solution; then, a certain proportion of heat-expandable microsphere foaming agent is added to the cross-linked flame-retardant cellulose ionic liquid solution and stirred to obtain spinning solution, then the spinning solution is filtered and degassed in sequence and placed in a wet spinning device, and the spinning solution is extruded from the spinneret under a nitrogen pressure of 0.5 MPa, and flame-retardant prefabricated fibers are obtained through coagulation, hot stretching, cutting, oiling, packaging and other processes;
[0081] Step 2, spinning of blended yarn: the flame retardant prefabricated fiber is mixed with the high-performance flame retardant fiber, the flame retardant super absorbent fiber, and the flame retardant superfine hydrophobic fiber respectively, and the three mixtures are respectively subjected to the processes of oiling and moistening, premixing, carding and combing, drawing, roving, spun yarn, winding, doubling, twisting, and steaming yarn to spin yarn I, yarn II, and yarn III respectively;
[0082] Step 3, preparation of base fabric: through fabric structure design, yarn I, yarn II and yarn III are warped, sizing, reeded, weaved and repaired in sequence to obtain a multi-layer base fabric, wherein the outermost layer of the multi-layer base fabric is a flame retardant layer composed of yarn I, the middle layer is a super absorbent layer composed of yarn II, and the innermost layer is a hydrophobic comfort layer composed of yarn III;
[0083] Step 4, preparation of lightweight high-heat protective material: After the base fabric prepared in step 3 is desized, dyed, and stretched and shaped, the inner surface of the fabric is then subjected to a sanding process, and then subjected to a high-temperature treatment, so that the heat-expandable microsphere foaming agent evenly distributed in the flame-retardant prefabricated fiber matrix expands when heated to form a multi-dimensional lightweight high-heat protective material.
[0084] The cross-linked flame-retardant cellulose ionic liquid solution in step 1 contains 25 parts of nanosol composite smoke suppression flame retardant, 5 parts of cross-linking agent, and the rest is cellulose ionic liquid solution.
[0085] The spinning stock solution in step 1 contains 10 parts of heat-expandable microsphere foaming agent, the average particle size of the heat-expandable microsphere foaming agent is 350 nm; the rest is cross-linked flame-retardant cellulose ionic liquid solution.
[0086] The nanosol composite smoke suppressant and flame retardant described in step 1 contains 20 parts of bisphenol-modified phosphate ester polymer, 10 parts of hydroxymethylphosphonic acid guanidine, 20 parts of phosphorus heterocyclic methoxy, 15 parts of ferrous oxalate, 25 parts of calcium phosphomolybdate and 10 parts of dihydroxy metal composite oxide-magnesium aluminum hydroxide. The average particle size of the nanosol composite smoke suppressant and flame retardant is 260nm.
[0087] The cross-linking agent in step 1 comprises 45 parts of ammonium bicarbonate and 55 parts of ammonium acetate.
[0088] In the hot stretching process described in step 1, the hot stretching temperature is 110° C. and the stretching ratio is 1.5 times.
[0089] The yarn I described in step 2 comprises 30 parts of flame-retardant prefabricated fibers, 35 parts of polyphenylene sulfide fibers, and 35 parts of polyimide fibers.
[0090] The yarn II described in step 2 contains 35 parts of flame-retardant super absorbent fiber, 35 parts of flame-retardant prefabricated fiber, 20 parts of meta-aramid and 10 parts of para-aramid.
[0091] The yarn III described in step 2 contains 30 parts of flame-retardant ultrafine hydrophobic fibers, 40 parts of flame-retardant prefabricated fibers, 20 parts of meta-aramid fibers, and 10 parts of para-aramid fibers.
[0092] The linear density of yarn I described in step 2 is 11.81 tex×2, the linear density of yarn II is 9.84 tex×2, and the linear density of yarn III is 11.81 tex×2.
[0093] The yarn steaming process temperature in step 2 is 80°C.
[0094] The fabric structure described in step 3 is formed by the middle layer being interwoven with the outer layer and the inner layer by means of inner warp knotting outer weft and outer warp knotting inner weft.
[0095] The fabric in step 3 has a warp density of 660 strands / 10 cm and a weft density of 575 strands / 10 cm.
[0096] The arrangement ratio of the outer layer, middle layer and inner layer fabric yarns in step 3 is 3:2:3.
[0097] The drying temperature of the sizing process described in step 3 is 100°C.
[0098] The mass per unit area of the base fabric described in step 3 is 300 g / m 2 The unit area mass ratio of the outer layer, middle layer and inner layer fabrics is 3:2:3.
[0099] The mesh number of the sanded sand leather described in step 4 is 500 meshes, the vehicle speed is 12 meters per minute, the grinding roller speed is 850 revs per minute, and the pressure is 0.2 MPa.
[0100] The temperature during the high temperature treatment in step 4 is 140°C.
[0101] Example 3
[0102] This embodiment provides a method for preparing a lightweight micro-nano porous three-dimensional high-heat protection material, the steps comprising:
[0103] Step 1, preparation of flame-retardant prefabricated fibers: first, nano-sol composite smoke suppression flame retardant and cross-linking agent are sequentially added to cellulose ionic liquid solution and stirred to obtain cross-linked flame-retardant cellulose ionic liquid solution; then, a certain proportion of heat-expandable microsphere foaming agent is added to the cross-linked flame-retardant cellulose ionic liquid solution and stirred to obtain spinning solution, then the spinning solution is filtered and degassed in sequence and placed in a wet spinning device, and the spinning solution is extruded from the spinneret under a nitrogen pressure of 0.5 MPa, and flame-retardant prefabricated fibers are obtained through coagulation, hot stretching, cutting, oiling, packaging and other processes;
[0104] Step 2, spinning of blended yarn: the flame retardant prefabricated fiber is mixed with the high-performance flame retardant fiber, the flame retardant super absorbent fiber, and the flame retardant superfine hydrophobic fiber respectively, and the three mixtures are respectively subjected to the processes of oiling and moistening, premixing, carding and combing, drawing, roving, spun yarn, winding, doubling, twisting, and steaming yarn to spin yarn I, yarn II, and yarn III respectively;
[0105] Step 3, preparation of base fabric: through fabric structure design, yarn I, yarn II and yarn III are warped, sizing, reeded, weaved and repaired in sequence to obtain a multi-layer base fabric, wherein the outermost layer of the multi-layer base fabric is a flame retardant layer composed of yarn I, the middle layer is a super absorbent layer composed of yarn II, and the innermost layer is a hydrophobic comfort layer composed of yarn III;
[0106] Step 4, preparation of lightweight high-heat protective material: After the base fabric prepared in step 3 is desized, dyed, and stretched and shaped, the inner surface of the fabric is then subjected to a sanding process, and then subjected to a high-temperature treatment, so that the heat-expandable microsphere foaming agent evenly distributed in the flame-retardant prefabricated fiber matrix expands when heated to form a multi-dimensional lightweight high-heat protective material.
[0107] The cross-linked flame-retardant cellulose ionic liquid solution in step 1 contains 15 parts of nanosol composite smoke suppression flame retardant, 3 parts of cross-linking agent, and the rest is cellulose ionic liquid solution.
[0108] The spinning stock solution in step 1 contains 20 parts of heat-expandable microsphere foaming agent, the average particle size of the heat-expandable microsphere foaming agent is 400 nm; the rest is cross-linked flame-retardant cellulose ionic liquid solution.
[0109] The nanosol composite smoke suppressant and flame retardant described in step 1 contains 15 parts of bisphenol-modified phosphate ester polymer, 15 parts of hydroxymethylphosphonic acid guanidine urea, 35 parts of phosphorus heterocyclic methoxy, 8 parts of ferrous oxalate, 15 parts of calcium phosphomolybdate and 12 parts of dihydroxy metal composite oxide-magnesium aluminum hydroxide. The average particle size of the nanosol composite smoke suppressant and flame retardant is 300nm.
[0110] The cross-linking agent in step 1 comprises 65 parts of ammonium bicarbonate and 35 parts of ammonium acetate.
[0111] In the hot stretching process described in step 1, the hot stretching temperature is 120° C. and the stretching ratio is 3.0 times.
[0112] The yarn I described in step 2 comprises 40 parts of flame-retardant prefabricated fibers, 40 parts of aromatic sulfone fibers, and 20 parts of polyimide fibers.
[0113] The yarn II described in step 2 contains 45 parts of flame-retardant super absorbent fibers, 40 parts of flame-retardant prefabricated fibers, and 15 parts of para-aramid fibers.
[0114] The yarn III described in step 2 contains 35 parts of flame-retardant ultrafine hydrophobic fibers, 40 parts of flame-retardant prefabricated fibers, 20 parts of meta-aramid fibers, and 5 parts of para-aramid fibers.
[0115] The linear density of yarn I described in step 2 is 11.81tex×2, the linear density of yarn II is 11.81tex×2tex, and the linear density of yarn III is 11.81tex×2.
[0116] The yarn steaming process temperature in step 2 is 90°C.
[0117] The fabric structure described in step 3 is formed by the middle layer being interwoven with the outer layer and the inner layer by means of inner warp knotting outer weft and outer warp knotting inner weft.
[0118] The fabric in step 3 has a warp density of 710 strands / 10 cm and a weft density of 590 strands / 10 cm.
[0119] The arrangement ratio of the outer layer, middle layer and inner layer fabric yarns in step 3 is 1:1:1.
[0120] The drying temperature of the sizing process described in step 3 is 110°C.
[0121] The mass per unit area of the base fabric described in step 3 is 330 g / m 2 The unit area mass ratio of the outer layer, middle layer and inner layer fabrics is 3:2:2.
[0122] The mesh number of the sanded sand leather described in step 4 is 450 meshes, the vehicle speed is 15 meters per minute, the grinding roller speed is 900 revs per minute, and the pressure is 0.3 MPa.
[0123] The temperature during the high temperature treatment in step 4 is 150°C.
[0124] Example 4
[0125] This embodiment provides a method for preparing a lightweight micro-nano porous three-dimensional high-heat protection material, the steps comprising:
[0126] Step 1, preparation of flame-retardant prefabricated fibers: first, nano-sol composite smoke suppression flame retardant and cross-linking agent are sequentially added to cellulose ionic liquid solution and stirred to obtain cross-linked flame-retardant cellulose ionic liquid solution; then, a certain proportion of heat-expandable microsphere foaming agent is added to the cross-linked flame-retardant cellulose ionic liquid solution and stirred to obtain spinning solution, then the spinning solution is filtered and degassed in sequence and placed in a wet spinning device, and the spinning solution is extruded from the spinneret under a nitrogen pressure of 0.5 MPa, and flame-retardant prefabricated fibers are obtained through coagulation, hot stretching, cutting, oiling, packaging and other processes;
[0127] Step 2, spinning of blended yarn: the flame retardant prefabricated fiber is mixed with the high-performance flame retardant fiber, the flame retardant super absorbent fiber, and the flame retardant superfine hydrophobic fiber respectively, and the three mixtures are respectively subjected to the processes of oiling and moistening, premixing, carding and combing, drawing, roving, spun yarn, winding, doubling, twisting, and steaming yarn to spin yarn I, yarn II, and yarn III respectively;
[0128] Step 3, preparation of base fabric: through fabric structure design, yarn I, yarn II and yarn III are warped, sizing, reeded, weaved and repaired in sequence to obtain a multi-layer base fabric, wherein the outermost layer of the multi-layer base fabric is a flame retardant layer composed of yarn I, the middle layer is a super absorbent layer composed of yarn II, and the innermost layer is a hydrophobic comfort layer composed of yarn III;
[0129] Step 4, preparation of lightweight high-heat protective material: After the base fabric prepared in step 3 is desized, dyed, and stretched and shaped, the inner surface of the fabric is then subjected to a sanding process, and then subjected to a high-temperature treatment, so that the heat-expandable microsphere foaming agent evenly distributed in the flame-retardant prefabricated fiber matrix expands when heated to form a multi-dimensional lightweight high-heat protective material.
[0130] The cross-linked flame-retardant cellulose ionic liquid solution in step 1 contains 20 parts of nanosol composite smoke suppression flame retardant, 5 parts of cross-linking agent, and the rest is cellulose ionic liquid solution.
[0131] The spinning stock solution in step 1 contains 20 parts of heat-expandable microsphere foaming agent, the average particle size of the heat-expandable microsphere foaming agent is 300 nm; the rest is cross-linked flame-retardant cellulose ionic liquid solution.
[0132] The nanosol composite smoke suppressant and flame retardant described in step 1 contains 10 parts of bisphenol-modified phosphate ester polymer, 20 parts of hydroxymethylphosphonic acid guanidine, 30 parts of phosphorus heterocyclic methoxy, 10 parts of ferrous oxalate, 15 parts of calcium phosphomolybdate and 15 parts of dihydroxy metal composite oxide-magnesium aluminum hydroxide. The average particle size of the nanosol composite smoke suppressant and flame retardant is 200nm.
[0133] The cross-linking agent in step 1 comprises 55 parts of ammonium bicarbonate and 45 parts of ammonium acetate.
[0134] In the hot stretching process described in step 1, the hot stretching temperature is 120° C. and the stretching ratio is 2.0 times.
[0135] The yarn I described in step 2 comprises 45 parts of flame-retardant prefabricated fibers, 20 parts of aromatic sulfone fibers, and 35 parts of polyphenylene sulfide fibers.
[0136] The yarn II described in step 2 contains 30 parts of flame-retardant super absorbent fiber, 40 parts of flame-retardant prefabricated fiber, 25 parts of meta-aramid and 5 parts of para-aramid.
[0137] The yarn III described in step 2 contains 35 parts of flame-retardant ultrafine hydrophobic fibers, 40 parts of flame-retardant prefabricated fibers, 20 parts of meta-aramid fibers, and 5 parts of para-aramid fibers.
[0138] The linear density of yarn I described in step 2 is 15.54 tex×2, the linear density of yarn II is 10.74 tex×2, and the linear density of yarn III is 11.81 tex×2.
[0139] The yarn steaming process temperature in step 2 is 90°C.
[0140] The fabric structure described in step 3 is formed by the middle layer being interwoven with the outer layer and the inner layer by means of inner warp knotting outer weft and outer warp knotting inner weft.
[0141] The fabric in step 3 has a warp density of 685 strands / 10 cm and a weft density of 625 strands / 10 cm.
[0142] The arrangement ratio of the outer layer, middle layer and inner layer fabric yarns in step 3 is 4:2:3.
[0143] The drying temperature of the sizing process described in step 3 is 110°C.
[0144] The mass per unit area of the base fabric described in step 3 is 360 g / m 2 The unit area mass ratio of the outer layer, middle layer and inner layer fabrics is 4:2:3.
[0145] The mesh number of the sanded sand leather described in step 4 is 450 meshes, the vehicle speed is 18 meters per minute, the grinding roller speed is 900 revs per minute, and the pressure is 0.4 MPa.
[0146] The temperature during the high temperature treatment in step 4 is 160°C.
[0147] Comparative Example 1
[0148] A method for preparing a three-dimensional high-heat protective material, wherein in step 4, after the inner surface of the fabric is subjected to sanding processing, no high-temperature treatment is performed, and the rest is the same as in Example 1.
[0149] Comparative Example 2
[0150] A method for preparing a lightweight micro-nano porous three-dimensional high-heat protective material, in which the mass ratio of bisphenol-modified phosphate ester oligomer, hydroxymethylphosphonic acid guanidine urea and phosphorus heterocyclic methoxy in the nanosol composite smoke suppression flame retardant described in step 1 is 1:2:3, and other process conditions are the same as those in Example 1.
[0151] Comparative Example 3
[0152] A method for preparing a lightweight micro-nano porous three-dimensional high-heat protective material, wherein in the nanosol composite smoke suppression flame retardant described in step 1, the mass ratio of bisphenol-modified phosphate ester polymer, hydroxymethyl phosphoguanidine, phosphorus heterocyclomethoxy, ferrous oxalate, calcium phosphomolybdate and dihydroxy metal composite oxide-magnesium aluminum hydroxide is 1:1:1:1:1:1, and other process conditions are the same as those in Example 1.
[0153] Comparative Example 4
[0154] A method for preparing a lightweight micro-nano porous three-dimensional high-heat protective material, wherein in step 1, the cross-linking agent in the cross-linked flame-retardant cellulose ionic liquid solution is 0 parts, and other process conditions are the same as those in Example 1.
[0155] The lightweight micro-nano porous three-dimensional high-heat protective materials prepared in Examples 1-4 and Comparative Examples 1-4 were washed 100 times using an A2 automatic washing machine with a neutral detergent and in accordance with the 4N method in GB / T 8629-2017, and then tested for flame retardancy and heat insulation properties in accordance with the standards GB 8965.1-2020 "Protective Clothing Flame Retardant Clothing" and GB 38453-2019 "Protective Clothing Heat Insulation Clothing"; and tested for smoke suppression performance (maximum specific optical density) of protective materials in accordance with GB / T10671-2008 "Test Method for Specific Optical Density of Smoke Generated by Solid Materials". The measured data of various technical indicators are shown in Table 1.
[0156] Table 1 Test results of various indicators of lightweight micro-nano porous three-dimensional high-heat protection materials
[0157]
[0158] By comparing and analyzing the test data of the lightweight micro-nano porous three-dimensional high-heat protection material prepared in Example 1 and Comparative Example 1, it can be seen that when the final protection material is not subjected to high-temperature treatment, the heat-expandable material evenly distributed in the material does not expand, resulting in a sharp drop in the heat protection coefficient of the protection material. The heat protection coefficient of the protection material after heat expansion (Example 1) is 1878kW·s / m 2 The thermal protection coefficient of the unexpanded protective material (Comparative Example 2) is 1189kW·s / m 2It can be seen that the thermal protection coefficient of the protective material can be increased by 58.7% after the final fabric is expanded after high-temperature treatment, and the technical advantage is obvious. At the same time, by comparing and analyzing the thermal insulation performance, it is found that when the protective material (Comparative Example 1) is not subjected to high-temperature treatment, its convective heat conduction level is B2, the radiant heat conduction level is C2, and the contact heat conduction level is F2. After high-temperature treatment and expansion, the convective heat conduction level of the protective material (Example 1) is B3, the radiant heat conduction level is C3, and the contact heat conduction level is F3, and its technical advantage is obvious. In addition, by comparing and analyzing the thermal protection and thermal insulation performance of Examples 1-4, the technical index values are positively correlated with the content of the flame-retardant prefabricated fiber. It can be seen that the flame-retardant prefabricated fiber prepared by the present invention significantly improves the comprehensive performance of the protective material without increasing the technical difficulty.
[0159] By comparing and analyzing the test data of the protective materials prepared in Example 1 and Comparative Example 2, it can be seen that when the smoke suppression type flame retardant (ferrous oxalate, calcium phosphomolybdate and dihydroxy metal composite oxide-magnesium aluminum hydroxide) is not added to the flame retardant, the maximum specific optical density of the protective material (Comparative Example 2) after combustion is 3.42 times that of the material with the smoke suppression type flame retardant. It can be seen that the present invention changes its combustion mode through the flame retardant-smoke suppression synergistic effect, relying on the flame retardant principles such as covering effect, transfer effect, inhibition of free radicals, and accelerated carbonization, and reduces the amount of smoke by reducing the content of combustibles. By utilizing the synergistic effect, a composite smoke suppression and flame retardant effect (Example 1) is achieved.
[0160] By comparing and analyzing the flame retardant and thermal protection test data of the protective materials prepared in Example 1 and Comparative Example 3, it can be seen that when the quality of the flame retardant components is set equal (Comparative Example 3), the flame retardant and thermal insulation properties of the protective material are far inferior to those of Example 1. It can be seen that there is a flame retardant synergistic effect between the components of the flame retardant, and the content will also affect the flame retardant and thermal protection properties of the composite fabric.
[0161] By comparing and analyzing the test data of the protective materials prepared in Example 1 and Comparative Example 4, it can be seen that when no cross-linking agent is added to the cellulose ionic liquid solution system, after 100 washes, the flame retardant properties and smoke suppression properties of the prepared protective material (Comparative Example 4) are greatly reduced. It can be seen that the addition of the cross-linking agent (Example 1) not only makes the homemade flame retardant prefabricated fiber have excellent mechanical properties, but also has good spinnability when not subjected to heating and expansion treatment. Theoretically, there is no upper limit to the amount of addition. After subsequent high-temperature treatment, the fabric can distribute more micro-nano porous structures, making the fabric lightweight and highly heat-protective, and can also improve the material's washing resistance, extend the service life, and reduce the cost of use.
[0162] The principles, steps, etc. not explicitly described in the present invention are all obtainable by those skilled in the art through conventional technical means, and therefore are not described in detail. Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a lightweight micro-nano porous three-dimensional high-heat protection material, characterized in that the steps include: (1) Preparation of flame-retardant prefabricated fibers: First, a nano-sol composite smoke suppression flame retardant and a cross-linking agent are sequentially added to a cellulose ionic liquid solution and stirred to obtain a cross-linked flame-retardant cellulose ionic liquid solution; then, a certain proportion of a heat-expandable microsphere foaming agent is added to the cross-linked flame-retardant cellulose ionic liquid solution and stirred to obtain a spinning solution; then, the spinning solution is filtered and degassed in sequence and placed in a wet spinning device; the spinning solution is extruded from a spinneret under a nitrogen pressure of 0.5 MPa; and flame-retardant prefabricated fibers are obtained through processes such as coagulation, hot stretching, cutting, oiling, and packaging; (2) Spinning of blended yarns: flame-retardant prefabricated fibers are mixed with high-performance flame-retardant fibers, flame-retardant super absorbent fibers, and flame-retardant superfine hydrophobic fibers, respectively. The three mixtures are subjected to the processes of oiling and moistening, premixing, carding and combing, drawing, roving, spinning, winding, doubling, twisting, and steaming to respectively spin yarn I, yarn II, and yarn III; (3) Preparation of base fabric: through the design of fabric structure, yarn I, yarn II and yarn III are warped, sizing, reeded, woven and trimmed in sequence to obtain a multi-layer base fabric, wherein the outermost layer of the multi-layer base fabric is a flame retardant layer composed of yarn I, the middle layer is a super absorbent layer composed of yarn II, and the innermost layer is a hydrophobic comfort layer composed of yarn III; (4) Preparation of lightweight high-heat protective material: The base fabric prepared in step 3 is subjected to desizing, dyeing, and stentering treatments, and then the inner surface of the fabric is subjected to sanding processing. Finally, it is subjected to high-temperature treatment so that the heat-expandable microsphere foaming agent evenly distributed in the flame-retardant prefabricated fiber matrix expands upon heat to form a multi-dimensional lightweight high-heat protective material.
2. The method for preparing a lightweight micro-nano porous three-dimensional high-heat protection material according to claim 1, characterized in that: The cross-linked flame-retardant cellulose ionic liquid solution contains 15 to 25 parts of nano-sol composite smoke suppression flame retardant, 3 to 5 parts of cross-linking agent, and the rest is cellulose ionic liquid.
3. The method for preparing a lightweight micro-nano porous three-dimensional high-heat protection material according to claim 1, characterized in that: The spinning stock solution contains 10 to 25 parts of a heat-expandable microsphere foaming agent, the average particle size of which is 300 nm to 400 nm; and the rest is a cross-linked flame-retardant cellulose ionic liquid solution.
4. The method for preparing a lightweight micro-nano porous three-dimensional high-heat protection material according to claim 1, characterized in that: The nano-sol composite smoke suppression flame retardant comprises a mixture of bisphenol modified phosphate ester oligomer, hydroxymethyl phosphonic acid guanidine urea, phosphorus heterocyclic methoxy, ferrous oxalate, calcium phosphomolybdate and dihydroxy metal composite oxide-magnesium aluminum hydroxide.
5. The method for preparing a lightweight micro-nano porous three-dimensional high-heat protection material according to claim 1, characterized in that: The nano-sol composite smoke suppression and flame retardant comprises 10 to 20 parts of bisphenol-modified phosphate ester oligomer, 10 to 20 parts of hydroxymethylphosphonic acid guanidine urea, 20 to 35 parts of phosphorus heterocyclic methoxy, 8 to 15 parts of ferrous oxalate, 15 to 25 parts of calcium phosphomolybdate, and 8 to 15 parts of dihydroxy metal composite oxide-magnesium aluminum hydroxide, and the average particle size is 200 nm to 300 nm.
6. The method for preparing a lightweight micro-nano porous three-dimensional high-heat protection material according to claim 1, characterized in that: The cross-linking agent contains 45 to 65 parts of ammonium bicarbonate and 35 to 55 parts of ammonium acetate, the hot stretching temperature is 110° C. to 120° C., and the stretching multiple is 1.5 to 3.0 times; the high-performance flame-retardant fiber includes a mixture of various fibers including aromatic sulfone fiber, polyphenylene sulfide fiber, polyimide fiber, meta-aramid fiber and para-aramid fiber.
7. The method for preparing a lightweight micro-nano porous three-dimensional high-heat protection material according to claim 1, characterized in that: The yarn I contains 30 to 50 parts of flame-retardant prefabricated fibers, 20 to 40 parts of aromatic sulfone fibers, 25 to 45 parts of polyphenylene sulfide fibers, and 25 to 40 parts of polyimide fibers; The yarn II contains 25 to 45 parts of flame-retardant super absorbent fiber, 30 to 50 parts of flame-retardant prefabricated fiber, 20 to 50 parts of meta-aramid fiber, and 5 to 15 parts of para-aramid fiber; The yarn III contains 25 to 45 parts of flame-retardant ultrafine hydrophobic fibers, 30 to 50 parts of flame-retardant prefabricated fibers, 20 to 50 parts of meta-aramid fibers, and 5 to 15 parts of para-aramid fibers.
8. The method for preparing a lightweight micro-nano porous three-dimensional high-heat protection material according to claim 1, characterized in that: The linear density of the yarn I is 11.81tex×2 to 15.54tex×2, the linear density of the yarn II is 9.84tex×2 to 11.81tex×2, and the linear density of the yarn III is 11.81tex×2 to 13.12tex×2. The temperature of the yarn steaming process is 80℃ to 100℃.
9. The method for preparing a lightweight micro-nano porous three-dimensional high-heat protection material according to claim 1, characterized in that: The warp density of the fabric is 660 to 710 strands / 10cm, and the weft density is 575 to 625 strands / 10cm; the yarn arrangement ratio of the outer layer, middle layer, and inner layer is 1:1:1 to 4:2:3; the drying temperature of the sizing process is 100°C to 120°C; the unit area mass of the base fabric is 300g / m 2 ~360g / m 2 The mesh size of the sandpaper is 400 to 500, the vehicle speed is 12 m / min to 18 m / min, the grinding roller speed is 850 rpm to 950 rpm, and the pressure is 0.2 MPa to 0.4 MPa; the high temperature treatment temperature is 140°C to 160°C.
10. A lightweight micro-nano porous three-dimensional high-heat protective material prepared by the preparation method described in any one of claims 1 to 9.
Citation Information
Patent Citations
A method for preparing a fire-resistant and heat-insulating metallized coated fabric
CN108221397B
Modacrylic fiber blended flame-retardant high-temperature-resistant antistatic fabric and preparation method thereof
CN109208154A
A flame-retardant and heat-insulating fabric for fire escape emergency and its production device
CN112221027B
Thermal protection fabric with multi-dimensional composite structure and preparation method of thermal protection fabric
CN116423938A
Cited By
Flame-retardant, heat-insulating and molten metal impact-resistant electric welding protective clothing fabric
CN120945551A